A Comparison of the Perceptions of Need Satisfaction and Need Frustration Between Racialized and Non-Racialized Undergraduate Students - Oram, Rylee; Sullivan, Rebecca; Rogers, Maria (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2023)
Research has demonstrated that racialized students experience additional stressors during post-secondary education compared to their white counterparts. These barriers can include added institutional barriers, lower representation among faculty, additional stress associated with cultural differences and stigmatization, discrimination, and racism. According to self-determination theory, students who experience an unsupportive or controlling environment are more likely to have lower basic psychological need satisfaction, lower academic motivation, and lower well-being. The current study aimed to examine whether white and racialized students would differ in their perceptions of need satisfaction and need frustration in their learning environment. Participants were undergraduate students (N = 712) from a large Canadian university. A one-way MANCOVA was performed comparing racialized and white students on basic psychological need satisfaction and frustration with gender as a covariate. Results suggested that racialized students perceived lower autonomy satisfaction, lower competence satisfaction, and higher relatedness frustration in their learning environment. These findings present important implications for higher education institutions. Institutions should recognize the diverse needs of their student population and ensure that learning environments are supportive of these needs, as they can have significant detrimental impacts on the overall well-being and academic success of these students.